2019
DOI: 10.1016/j.devcel.2019.02.002
|View full text |Cite
|
Sign up to set email alerts
|

The Kinetochore-Microtubule Coupling Machinery Is Repurposed in Sensory Nervous System Morphogenesis

Abstract: Summary Dynamic coupling of microtubule ends to kinetochores, built on the centromeres of chromosomes, directs chromosome segregation during cell division. Here, we report that the evolutionarily ancient kinetochore-microtubule coupling machine, the KMN (Knl1/Mis12/Ndc80-complex) network, plays a critical role in neuronal morphogenesis. We show that the KMN network concentrates in microtubule-rich dendrites of developing sensory neurons that collectively extend in a multicellular morphogenetic event… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
57
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 41 publications
(69 citation statements)
references
References 40 publications
(53 reference statements)
3
57
0
Order By: Relevance
“…We hypothesize that post-translational modifications in the amino-terminal domain of Spindly may regulate its role in neurodevelopment. Recently it has been reported that other kinetochore proteins are important for neurodevelopment (30, 31) [reviewed in (32)]. For example, depletion of Mis12, Knl1 and Ndc80 (other kinetochore components) results in abnormal neuromuscular junctions and central nervous system development both in Drosophila and in C. elegans (30, 31).…”
Section: Discussionmentioning
confidence: 99%
“…We hypothesize that post-translational modifications in the amino-terminal domain of Spindly may regulate its role in neurodevelopment. Recently it has been reported that other kinetochore proteins are important for neurodevelopment (30, 31) [reviewed in (32)]. For example, depletion of Mis12, Knl1 and Ndc80 (other kinetochore components) results in abnormal neuromuscular junctions and central nervous system development both in Drosophila and in C. elegans (30, 31).…”
Section: Discussionmentioning
confidence: 99%
“…Lastly, in C. elegans, Drosophila, and iPS-derived human motor neurons, some or all of the core kinetochore proteins localize to the regions of synaptic neuropil and axons that are devoid of nuclei. There they control axon outgrowth and dendritic extension in the developing sensory nervous system (Cheerambathur et al 2019;Zhao et al 2019). All of these examples highlight that the timing and location of kinetochore assembly are tuned to the cell cycle and cell type.…”
Section: Cells Customize Kinetochore Activity By Controlling Kinetochmentioning
confidence: 99%
“…32). For example, depletion of Mis12, Knl1, and Ndc80 (other kinetochore components) results in abnormal neuromuscular junctions and central nervous system development both in Drosophila and in Caenorhabditis elegans (30,31). However, the precise roles of these kinetochore proteins in neurodevelopment are as yet unknown.…”
Section: Discussionmentioning
confidence: 99%